Da vida dos arquivos anarquistas contemporâneos no Brasil - Passetti, Edson (Ecopolítica, 2013)
A retomada dos anarquismos após a ditadura civil-militar mostra suas diversidades e variadas implicações políticas diante do ingovernável. O artigo situa a produção dos arquivos anarquistas como arquivo monumento voltada a práticas libertárias na atualidade. Discute a importância da universidade para os anarquismos contemporâneos, as implicações relativas ao uso da Internet e situa o momento da produção da verdade anarquista. Palavras-chave: anarquismos; arquivos; universidade; internet; ingovernável On the life of contemporary anarchist archives in Brazil Abstract: The retaking of the anarchisms after the civil-military dictatorship shows their diversities and varied political implications facing the ungovernable. This article examines the production of anarchist archives as archive monument dedicated to today libertarian practices. The article discusses the importance of the university to the contemporary anarchism, the implications of the use of the Internet and it also analyzes the moment of the production of the anarchist truth. Keywords: anarchisms, archives, university, internet, ungovernable